The effects of fiscal rules on public investment over the cycle - Ekaterina Jürgens (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2022)
This paper investigates how numerical fiscal rules affect government investment in the EU and disentangles their effect over the business cycle. Public investment seems to be generally susceptible to cutbacks during recessions. Fiscal rules demonstrate heterogeneous effects, depending on their design and on the state of the economy. Specifically, rigid fiscal rules, lacking flexibility features, restrain government investment. This detrimental effect mostly materializes during a downturn, thus exacerbating the overall negative impact of the recession. Key public investment categories, such as Economic Affairs, Housing, Health, and Social Protection, shrink during recessions when fiscal rules are implemented. It is important to design fiscal rules with enough flexibility to reduce their procyclical effect and prevent them from curtailing investment in vital areas of public economy.
Keywords: E6; H5; H6; 330; Fiscal rules; public investment; fiscal cyclicality; EMU